Analysis on the status and development of quantum secure communication standardization - Junsen LAI; Bingbing WU; Rui TANG; Wenyu ZHAO; Haiyi ZHANG (Dianxin kexue)
Quantum secure communication based on quantum key distribution,which can provide theoretically unconditional security,is one of the effective solutions to ensure information security in the future.Recently,the application and industrialization of quantum secure communication in China has developed gradually,the demand for standardization has become increasingly apparent.The worldwide project plan,research status and development trend of quantum secure communication standardization were investigated,the problems and prospects of China’s standardization research were analyzed,and further suggestions to accelerate the standardization development were also proposed.